2021
DOI: 10.3390/ijerph18178897
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements—For Whom? The Current State of Knowledge about the Health Effects of Selected Supplement Use

Abstract: Dietary supplements are products containing nutrients sold in various medicinal forms, and their widespread use may stem from the conviction that a preparation that looks like a drug must have therapeutic properties. The aim of this scoping review is to present what is known about the effects of using selected dietary supplements in the context of chronic diseases, as well as the risks associated with their use. The literature shows that the taking of vitamin and mineral supplements by healthy people neither l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 134 publications
0
26
0
2
Order By: Relevance
“…In general, reports on the adverse events attributable to herbal or phytochemicals products are quite rare; the effects are generally mild and include headaches, nausea, and fatigue. More serious events, such as liver damage or bleeding, have also been described [ 114 , 116 ].…”
Section: Food Supplementsmentioning
confidence: 99%
“…In general, reports on the adverse events attributable to herbal or phytochemicals products are quite rare; the effects are generally mild and include headaches, nausea, and fatigue. More serious events, such as liver damage or bleeding, have also been described [ 114 , 116 ].…”
Section: Food Supplementsmentioning
confidence: 99%
“…Nesse sentido, embora a aparência frequentemente possa remeter a drogas e fármacos, os suplementos são classificados como produtos alimentares (27) .…”
Section: Benefícios Que a Adequada Suplementação Promove Ao Indivíduo...unclassified
“…Today, there are thousands of dietary supplements available on the market, including vitamins and minerals, plant ingredients and extracts, proteins and amino acids, omega-3 fatty acids, probiotics, and prebiotics [ 5 , 6 , 7 ]. Some research has indicated that dietary supplements can compensate for the nutritional deficit derived from unbalanced diets and can assist in prolonging the lifespan and provide some benefits in diseases, although evidence of direct effects is still insufficient [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%